Edukasi Pentingnya Konsumsi Tablet Fe pada Remaja di SMAS Adhyaksa 1 Kota Jambi - Nurfitriani, Nurfitriani; Nurita, Suci Rahmani; Yuliana, Yuliana (Universitas Baiturrahim, 2025)
Adolescent girls are one group of people who are vulnerable to anemia due to a lack of iron in their daily food consumption. Based on initial surveys, it was found that many young women suffer from anemia, one of which is due to a lack of consumption of vegetables and fruit. Teenagers prefer to eat foods that contain a lot of fat and sugar, they like instant food. The location chosen was Adyaksa 1 High School because the school is located in the city, densely populated and heterogeneous. The aim of the service was to determine the knowledge of young women about the importance of consuming Fe tablets and how and when to consume Fe tablets as an effort to prevent anemia at Adyaksa1 High School which was carried out in May 2024 for a total of 148 people. The activity begins with identifying partner problems, educational activities for young women about how and when to consume Fe tablets. Material is provided through lectures, giving leaflets and questions and answers with participants. Evaluation of the knowledge of young women before education is assessed by conducting a pretest, then they are given education once for 45-60 minutes. After the education ends, another evaluation is carried out in the form of a posttest with the same questions as the pretest. The results of the pretest and posttest with an average difference of 2-3 points, it can be concluded that there is an increase in knowledge of female students/adolescents in consuming fe tablets. Another expected output is the publication of the results of activities in the SINTA 5 accredited Health Services Journal (JAK).